Survival and immune responses of F1 transgenic tiger shrimp penaeus monodon against white spot syndrome virus (WSSV) - Parenrengi, Andi; Tenriulo, Andi; Tampangallo, Bunga Rante; Herlinah, Herlinah; Rosmiati, Rosmiati; Suryati, Emma; Alimuddin, Alimuddin; Lante, Samuel; Nawang, Agus; Suwardi, Suwardi; Hidayani, Andi Aliah (Penerbit Universiti Kebangsaan Malaysia, 2023)
Transgenic technology has been applied to tiger shrimp Peneus monodon to produce a resistant strain to white spot syndrome virus (WSSV) by antiviral gene overexpression. The founders (F0 ) transgenic tiger shrimp have been successfully bred to produce the first generation (F1 ). The present study aimed to evaluate the survival and immune responses of F1 transgenic tiger shrimp against WSSV. The F1 transgenic and non-transgenic shrimp (control) with an average weight of 7.93±1.49 g were collected from the controlled brackish water ponds and stocked in a 20 L fiberglass tank with a density of 5 shrimp/tank. The transgenic shrimps were confirmed by a PCR assay. The shrimp were intramuscularly injected with WSSV to evaluate the performance between transgenic and non-transgenic. The survival (SR) was observed daily after the challenge test. Measurement of immune responses, namely total haemocyte count (THC), differential haemocyte count (DHC), prophenoloxidase (proPO) activity, and RNA content in haemolymph was conducted on before challenge, and on the 1st, 3rd, and 5th days after challenge. The survival and immune responses were statistically analysed by the t-student test. The results showed that the SR of transgenic (52.0%), with a relative percentage survival of 47.82%, was greater (P<0.05) than the control shrimp (8.0%). The THC, proPO, and RNA content of the transgenic shrimp was higher (P<0.05) than the non-transgenic shrimp. The results suggested that the transgenic tiger shrimp, due to antiviral gene overexpression, increased the resistance against WSSV.